WOODWARD + MCDOWELL (Tufts Archival Research Center, 2007)
Woodward & McDowell proposal for management of the campaign to rescind San Francisco's anti-smoking ordinance. Discusses general elements of campaign plan. Focuses on vulnerabilities of the smoking law. States plan to use both grassroots advocacy and media campaigning. Allocates specific tasks to specific people. Describes committee to be organized to support the effort.